Characterization of proton pencil beam scanning and passive beam using a high spatial resolution solid‐state microdosimeter. Issue 11 (9th October 2017) - Tran, Linh T.; Chartier, Lachlan; Bolst, David; Pogossov, Alex; Guatelli, Susanna; Petasecca, Marco; Lerch, Michael L. F.; Prokopovich, Dale A.; Reinhard, Mark I.; Clasie, Benjamin; Depauw, Nicolas; Kooy, Hanne; et al.
Abstract : Purpose: This work aims to characterize a proton pencil beam scanning (PBS) and passive double scattering (DS) systems as well as to measure parameters relevant to the relative biological effectiveness (RBE) of the beam using a silicon on insulator (SOI) microdosimeter with well‐defined 3D sensitive volumes (SV). The dose equivalent downstream and laterally outside of a clinical PBS treatment field was assessed and compared to that of a DS beam. Methods: A novel silicon microdosimeter with well‐defined 3D SVs was used in this study. It was connected to low noise electronics, allowing for detection of lineal energies as low as 0.15 keV/μm. The microdosimeter was placed at various depths in a water phantom along the central axis of the proton beam, and at the distal part of the spread‐out Bragg peak (SOBP) in 0.5 mm increments. The RBE values of the pristine Bragg peak (BP) and SOBP were derived using the measured microdosimetric lineal energy spectra as inputs to the modified microdosimetric kinetic model (MKM). Geant4 simulations were performed in order to verify the calculated depth‐dose distribution from the treatment planning system (TPS) and to compare the simulated dose‐mean lineal energy to the experimental results. Results: For a 131 MeV PBS spot (124.6 mm R90 range in water), the measured dose‐mean lineal energy y D ¯ increased from 2 keV/μm at the entrance to 8 keV/μm in the BP, with a maximum value of 10 keV/μm at the distal edge. The derived RBE distribution for the PBS beam slowly increased from 0.97 ± 0.14 at the entrance to 1.04 ± 0.09 proximal to the BP, then to 1.1 ± 0.08 in the BP, and steeply rose to 1.57 ± 0.19 at the distal part of the BP. The RBE distribution for the DS SOBP beam was approximately 0.96 ± 0.16 to 1.01 ± 0.16 at shallow depths, and 1.01 ± 0.16 to 1.28 ± 0.17 within the SOBP. The RBE significantly increased from 1.29 ± 0.17 to 1.43 ± 0.18 at the distal edge of the SOBP. Conclusions: The SOI microdosimeter with its well‐defined 3D SV has applicability in characterizing proton radiation fields and can measure relevant physical parameters to model the RBE with submillimeter spatial resolution. It has been shown that for a physical dose of 1.82 Gy at the BP, the derived RBE based on the MKM model increased from 1.14 to 1.6 in the BP and its distal part. Good agreement was observed between the experimental and simulation results, confirming the potential application of SOI microdosimeter with 3D SV for quality assurance in proton therapy.